Magic with everyday objects over 150 tricks anyone can do at the dinner table - Schindler, George (New York : Stein and Day, 1976)
Directions for performing easy-to-do magic tricks without sleight of hand, using everyday objects.
Includes index.
Bibliography: p. 237.
Keywords: Magic tricks